Effect of vitamin K supplementation on anthropometric parameters and adipokine levels – a systematic review: Vitamin K and anthropometric parameters - Jamka, Małgorzata; Walach, Harald; Hołubiec, Magdalena; Wasiewicz, Maria; Walkowiak, Jarosław (Journal of Medical Science, 2019)
Aim. The aim of this systematic review was to assess the effect of vitamin K supplementation on anthropometric parameters and adipokine levels in adults.Material and Methods. Four databases (PubMed, Web of Sciences, Scopus and the Cochrane Library) were searched to select studies in which the effect of vitamin K supplementation on body weight, body mass index (BMI), fat mass, leptin and adiponectin levels were assessed.Results. We identified nine studies that included a total of 542 subjects. Vitamin K supplementation did not influence body weight, BMI and percentage of fat mass. In addition, the effect of vitamin K supplementation on adipokines levels was equivocal. Conclusions. Vitamin K supplementation did not affect anthropometric parameters and adipokines levels. Nevertheless, further studies are needed to clarify the effect of vitamin K supplementation on these parameters in adults.
Keywords: vitamin K; dietary supplements; body weight; leptin; adiponectin